A new class of signals for magnetobiology research - Makinistian, Leonardo (2019)
The great majority of experimental and theoretical studies in magnetobiology explored and tried to explain bioeffects on organisms (ranging from bacteria to humans) upon exposure to variable (AC) magnetic fields (MF) with a pure sinusoidal waveform, typically combined with a static (DC) component. In this report, a new class of signals is presented and posed as a relevant candidate for research in magnetobiology. The proposed signals are derived within the classic theory of the precession of a magnetic moment in a DC + AC MF in a parallel configuration. They display a frequency modulation such that the phase change per unit time of the applied AC field is, at all times, identical to that of the precession of the magnetic moment to which the field was tuned (considering its gyromagnetic ratio). In other words, applied AC field and precession of the ‘engaged’ magnetic moment are phase-locked. These phase-locked frequency modulated (PLFM) signals are discussed in the context of current literature, and possible future experimental and theoretical developments are suggested.